SOSIALISASI DAN PELATIHAN PENYARING AIR SEDERHANA DALAM MEWUJUDKAN SISTEM AIR BERSIH DI DESA KARANG INDAH - Nurhidayat, Aan; Abidin, Dindin; Ridlo, Azi Faiz (An-Nizam, 2024)
The socialization and training of simple water filters in Karang Indah Village is an initiative that aims to improve community access to clean water. The program is designed to empower villagers with the knowledge and skills to build and operate simple water filters. The socialization conducted includes understanding the importance of clean water, the negative impacts of contaminated water, and the benefits of water filtration. Hands-on training focused on the construction and maintenance of water filters using local materials easily found in the village. Participatory and interactive methods were applied to ensure the active involvement of all levels of the community, including youth, housewives, and village leaders. Thus, Bojongmangu Village is expected to be self-sufficient in meeting its clean water needs, creating a healthier environment, and reducing the risk of water-related diseases. This program not only creates infrastructure, but also builds community capacity and awareness of the importance of clean and safe water sources.